Peran Instagram dalam Memperkuat Branding Personal Bupati Mojokerto - Harun Askhari; M. Alfin Fatikh (Bahasa Indonesia, 2025)
This study examines the role of Instagram in strengthening the personal branding of Muhammad Al Barra (Gus Barra), the elected Regent of Mojokerto Regency. The research employs a qualitative case study approach, combining in-depth interviews, field observations, and documentation of Gus Barra’s official Instagram account (@gusbarra_). Data were collected from interviews with Gus Barra’s media team (Ahmad Solihin and Ahmad Tabrani), three community respondents (aged 24, 28, and 30), as well as the internal survey division of the Indonesian Survey Institute (LSI) that supported Gus Barra’s campaign. The findings reveal that Instagram functions as a highly effective political communication tool. The account consistently posted 1–2 pieces of content daily, with themes ranging from religious and social activities to community development programs. Based on LSI’s internal survey and field interviews, approximately 75% of Gus Barra’s voters—equivalent to around 279,400 out of 372,537 valid votes—reported that they became more familiar with Gus Barra through social media compared to conventional campaign methods. Gus Barra’s personal branding strategy follows Tom Peters’ model, consisting of self-assessment, brand identity development, strategic positioning, and promotion. Beyond visuals, captions in each post also played a key role. The messages conveyed were predominantly moral, religious, and socially oriented, such as calls for gratitude, the importance of mutual cooperation, and care for the underprivileged. Direct interaction through Instagram Direct Message (DM) further reinforced these messages by providing a personal and attentive impression. This study concludes that social media, particularly Instagram, functions not only as an information-sharing platform but also as a strategic instrument for building leadership legitimacy, enhancing electability, and fostering emotional connection with constituents.